Intuitionistic fuzzy multi-polygroups - Onar, Serkan; Ersoy, Bayram Ali; Davvaz, Bijan; Hila, Kostaq (SPRINGER HEIDELBERG, 2022)
In recent years, intuitionistic fuzzy multisets and polygroup have become a subject of great interest for researchers and have been widely applied to algebraic structures. In this paper, we introduce the concept of intuitionistic fuzzy multi-polygroups with the aid of algebraic structure of multi-polygroup in terms of intuitionistic fuzzy set theory. This new concept of polygroup as a connection between intuitionistic fuzzy multiset theory, set theory and polygroup theory displays the impact of intuitionistic fuzzy multisets on a polygroup structure. Operations on intuitionistic fuzzy multi-polygroups are introduced and several illustrative examples of them are provided. In addition to this, we investigate intuitionistic fuzzy normal multi-subpolygroups and some characterizations and algebraic properties of them are obtained. Moreover, homomorphisms of intuitionistic fuzzy multi-polygroups and some of their structural characteristics are discussed. Finally, we examine intuitionistic fuzzy quotient multi-polygroups.
Keywords: Multisets; Polygroups; Intuitionistic fuzzy multisets; Mathematics